Kajian aspek pertumbuhan ikan di perairan pedalaman Kabupaten Kutai Timur: Study on the aspect of fish growth at inland waters of East Kutai Regency - Muhammad Syahrir R. (Fakultas Perikanan dan Ilmu Kelautan, Universitas Mulawarman, 2022)
The study was conducted from October until November in 2012 at the Muara Bengkal and Muara Ancalong Sub District, East Kutai Regency. This study aims to determine the biological aspects of freshwater fish. The results showed that the growth pattern of fish species that positive allometric are repang (Osteochilus repang) and lepo (Ompok sabanus), while isometric growth pattern is fish giant sharkminnow (Osteochilus schlegelii) and the negative allometric pattern are climbing perch (Anabas testudineus), kelebere (Leiocassis stenomus) and kendia (Thynichthys vaillanti). Highest condition factor found in Lepo fish with 1:04 and lowest values found in climbing perch (Anabas testudineus) and giant sharkminnow (Osteochilus schlegelii) with a value of 1.01. Length of the growth equation, namely the collected climbing perch Lt = 226,8 (1-e - 1,6(t+1,25)), giant sharkminnow (Osteochilus schlegelii)Lt = 189,5 (1-e - 1,8(t+1,28)) kendia fish Lt = 163,23 (1-e -0,29(t+0,44)), repang fish 274,05 (1- e -0,79(t+0,96)), kelebere fish Lt = 221,03 (1-e -0,25 (t+0,41)), and Lepo fish Lt = 259,88 (1-e -0,63(t+0,85))..